1996
DOI: 10.1093/nar/24.12.2360
|View full text |Cite
|
Sign up to set email alerts
|

The Complete Nucleotide Sequence of Bacteriophage HP1 DNA

Abstract: The complete nucleotide sequence of the temperate phage HP1 of Haemophilus influenzae was determined. The phage contains a linear, double-stranded genome of 32 355 nt with cohesive termini. Statistical methods were used to identify 41 probable protein coding segments organized into five plausible transcriptional units. Regions encoding proteins involved in recombination, replication, transcriptional control, host cell lysis and phage production were identified. The sizes of proteins in the mature HP1 particle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 47 publications
0
51
0
Order By: Relevance
“…The genomes of phages HP1 and HP2 in Haemophilus influenzae (30), ⌽CTX in Pseudomonas aeruginosa (31), and K139 in Vibrio cholerae (32) have all been sequenced and shown to be P2-like with respect to genome organization as well as nucleotide sequence. Phages PSP3 in Salmonella enterica serovar Potsdam (33) and SopE⌽ in Salmonella enterica serovar Typhimurium (34) are also P2-like.…”
Section: Discussionmentioning
confidence: 99%
“…The genomes of phages HP1 and HP2 in Haemophilus influenzae (30), ⌽CTX in Pseudomonas aeruginosa (31), and K139 in Vibrio cholerae (32) have all been sequenced and shown to be P2-like with respect to genome organization as well as nucleotide sequence. Phages PSP3 in Salmonella enterica serovar Potsdam (33) and SopE⌽ in Salmonella enterica serovar Typhimurium (34) are also P2-like.…”
Section: Discussionmentioning
confidence: 99%
“…H0105 is similar to a hypothetical adenine-specific DNA methylase of bacteriophage HP1 (38% identity) (Esposito et al, 1996). It has been proposed that such a DNA modification is related to bacterial virulence (Heithoff et al, 1999).…”
Section: Identification Of the Attachment Site Of Vt2-sakaimentioning
confidence: 96%
“…Further sequence database searches with BLASTP+BEAUTY revealed that the protein encoded by ORF178 had significant homology with the lysozymes of Haemophilus influenzae phage HP1 (53 % similarity, 36 % identity; Benjamin et al, 1984;Esposito et al, 1996), E. coli phage P1 (51 % similarity, 33 % identity; Schmidt et al, 1996), APSE-1, a bacteriophage from an endosymbiont of the aphid Acyrthosiphon pisum (49 % similarity, 33 % identity; van der Wilk et al, 1999), and Salmonella typhimurium phage P22 (55 % similarity, 37 % identity; . The lysozymes from HP1, P1 (protein gp17), P22 (gp19) and APSE-1 (endolysin P13) share structurally conserved regions marked in the alignment with ORF178 (Fig.…”
Section: Sequence Analysis Of Orf178 and Orf119mentioning
confidence: 99%